Fused Thiazine Tethered Metal-Free Dyes for Dye Sensitized Solar Cells: A Computational Investigation - Gokula Krishnan, K.; Saravanan, V.; Udhaya Kumar, C.; Ramalingan, C. (Asian Journal of Chemistry, 2021)
Three novel cyanoacetamide decorated phenothiazines (1a-c) have been designed. Structural and photo-physical properties of the molecules 1a-c have been investigated. To better realize the charge transport process involved in the dye-sensitized solar cells (DSSCs), computational studies have been performed using B3LYP and CAM-B3LYP method for the dyes 1a-c. Theoretical findings for DSSCs include LHE (light-harvesting efficiency) and driving forces such as electron injection (ΔGinject) and dye regeneration have been calculated to envisage the most appropriate dyes for the application of DSSC.